Trends in the profile of non hodgkins lymphoma in North and South India: a study from two tertiary care hospitals in India - Sud, Rahul; Kumar, Kishore; Dubey, A. P.; Bhagat, Sagar (International Journal of Research in Medical Sciences, 2020)
Background: A number of environmental and chemical factors have been thought to been implicated in the occurrence of Non-Hodgkin’s Lymphomas (NHLs).To fill the knowledge gap in various aspect of the disease, this study was undertaken at this tertiary care centre in Delhi and Bangalore. Methods: This was a prospective observational study conducted in two defenses medical centre in India among patients of Non Hodgkins Lymphoma, registered at Command hospital Airforce Bangalore and Army Hospital (Research and Referral), New Delhi, between March 2016 and March 2019. Results: The disease showed a bimodal onset in both centres with 26 (26%) and 24 (24%) cases occurring in the age group of 31-40 years and 24 (24%) and 25 (25%) cases occurring in the age group of >60 years at CHAF (B) and AH (RR) respectively. B cell Lymphoma was the most common type of NHL seen in 85% and 89% patients, whereas T-cell lymphomas constituted 13% and 11% at CHAF (B) and AH (RR). 32(32%) patients presented with an Ann Arbor Stage 1 or 2 disease whereas 68(68%) patients were with Stage 3 or 4 disease at both the centers. IPI score was ≥3 in 45 % and 43% patients. Conclusions: NHL in India is a homogeneous and uniform disease. But there was increased detection of hepatosplenomegaly and associated hepatitis B/C in the southern part of India. Also, the occurrence of Cutaneous T cell lymphoma was only seen in the south India centre. The early stage NHLs has better survival and increase chance of complete response.